ADVERSE EFFECTS OF ALLOXAN ON THE BODY OF EXPERIMENTAL ANIMALS - Sanjar Yakubovich Mardonov (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Sugary diabetes treatment modern methods hypo - and hyperglycemia normal in the blood glucose to the level and diabetes complications development complete prevent to take opportunity does not give. β- cells replacement ( stomach) under diaper or β- cells transplant to do ) complications take comes , forever immunosuppressive therapy demand does and insulin independence every always also is not achieved , as well as donors noticeable at the level shortage available . Close until then endocrine part absolutely irreparable organ calculated stomach under diaper tissue update to the problem new look and reparative regeneration encouragement methods diabetes treatment and development prevent to take new methods open gives .